Алгоритм структурної ідентифікації об'єктів виробництва кальцинованої соди - Бобух, Анатолій Олексійович; Дзевочко, Олександр Михайлович; Подустов, Михайло Олексійович; Сляднєва, А. С. (НТУ "ХПІ", 2016)
В результате исследований разработан алгоритм структурной идентификации на базе метода пошаговой регрессии, который является экономичным с точки зрения необходимого для его реализации числа операций, способствует значительному повышению энергосбережения с улучшением качества управления за счет получения адекватного математического описания технологических объектов при разработке и внедрении компьютерно-интегрированного управления производством кальцинированной соды по аммиачному способу.

The algorithm of structural identification on the basis of a step-by-step regression method, which is economic from the viewpoint of operations number, necessary for its implementation, and which promotes substantial increase of energy saving with improvement of management quality due to obtaining the adequate mathematical description of technological objects at development and deployment of the soda ash computer integrated production man-agement on an ammoniac way, is developed as a result of researches.
Algorithm of soda ash production objects structural identification
Keywords: аміачний спосіб; ВКС; хіміко-технологічний об’єкт; нелінійні математичні моделі; алгоритм структурної ідентифікації; метод покрокової регресії; комп’ютерно-інтегроване управління